A Decision Tree Approach for Investment Decisions in SMEs - Ana Mufidah; Maheni Ika Sari; Nely Supeni (Budapest International Research and Critics University, 2022)
Small and Medium Enterprises (SMEs) are the most widely encountered businesses in Indonesia with various kinds of business fields engaged in by the community. Investment decisions are part of the activities carried out by SMEs. In making investment decisions are often influenced and based on various factors. A qualitative analysis research method used in this study. The research mechanism constructed is in the form of literature study. The literature used for citation consist of textbooks, articles, and online literature sources linked to this study. This article aims to produce a model that explains the factors that need to be considered in making investment decisions based on the literature and the results of previous empirical studies. In addition, the model uses a decision tree approach in making investment decisions for Small and Medium Enterprises (SMEs). The model produced in this study is sourced from various literatures that are used as a reference in the formation of models related to factors that need to be considered in making investment decisions in SMEs.